Experience and value perceived by the fashion brand followers in the Instagram (Revista de Ensino em Artes, Moda e Design, 2021)
This study investigated the nature of the experiences of fashion brand followers on Instagram. Based on Holbrook's (1999) axiology, we found in 21 in-depth interviews that perceived value is multidimensional, self-directed, hedonic, utilitarian and can be categorized into eight types: efficiency, excellence, esteem, status, ethical and epistemic. It has been found that all types are very relevant in the perception of the value of the brands
Keywords: Instagram; Perceived Value; Fashion Consumption